Association between dietary β-carotene intake with Parkinson’s disease and all-cause mortality among American adults aged 40 and older (NHANES 2001–2018) - Su, Jing; Liu, Liming; Wang, Ruonan; Li, Chunmei; Wang, Zihan; Xu, Qiaoli; Shen, Chunyu; Wu, Dalong; Zhao, Dexi (Frontiers in Nutrition, 2024)
The existing evidence concerning the correlation between dietary β-carotene intake and Parkinson's disease (PD) is currently deemed insufficient. Thus, this research aims to investigate the relationship between dietary β-carotene intake and both the prevalence of PD and all-cause mortality within the US(United States) population.: The research employed cross-sectional analysis and cohort studies utilizing data from 16852 participants in the National Health and Nutrition Examination Survey (NHANES) spanning from 2001 to 2018. Weighted logistic regression, weighted cox regression, restricted cubic splines(RCS), subgroup analysis, and sensitivity analyses were employed to validate the research objectives.Results: Among all eligible subjects, the mean age was 59.62±11.77 years, with a prevalence of PD at 1.82% overall, with 43.88% in males. In the fully adjusted model, dietary β-carotene intake exhibited a negative association with PD prevalence (odds ratio [OR] = 0.95; 95% confidence interval [CI]: 0.90~0.997; p = 0.040). Utilizing RCS analysis, a negative linear correlation between dietary β-carotene intake and PD prevalence was observed (non-linear p = 0.857). Furthermore, after controlling for multiple variables, dietary β-carotene intake was inversely associated with all-cause mortality (Hazard ratios [HR] = 0.98; 95% CI: 0.97~0.99; p = 0.002), with RCS curves indicating a negative linear relationship (nonlinear: p = 0.082). Comparable patterns of association were noted in subgroup analyses, and consistent findings were derived from additional sensitivity analyses.The cross-sectional and cohort study reveals a significant negative correlation between dietary β-carotene intake and both the prevalence of PD and all-cause mortality in the general population. This suggested that supplementing with dietary β-carotene might have certain benefits for reducing the prevalence of PD and all-cause mortality. However, further rigorously designed expected studies are needed to establish the causal relationship between them.